Case Report: Adrenal schwannoma associated with ganglioneuroma - He, Dong-Lin; Feng, Run-lin; Chai, Jia-gui; Guo, Xin; Ke, Chang-xing (Frontiers in Surgery, 2024)
BackgroundAn adrenal collision tumor (ACT) denotes the presence of distinct tumors with diverse behavioral, genetic, and histological features independently co-existing within the adrenal tissue without intermingling, and occurrences of such cases are infrequent. The concurrent occurrence of adrenal schwannoma and adrenal ganglioneuroma is exceedingly rare, and the diagnosis of these ACTs has been notably challenging due to their atypical clinical manifestations and imaging characteristics.Case summaryA 37-year-old man presented to the hospital 3 weeks after a computed tomography (CT) examination that revealed a left adrenal mass. Physical examination findings were unremarkable. Both CT and magnetic resonance imaging scans indicated the presence of a left adrenal mass. Plasma cortisol, adrenocorticotropic hormone, and renin–angiotensin–aldosterone system tests yielded normal results. Preoperative imaging confirmed the diagnosis of left adrenal pheochromocytoma. After thorough surgical preparation, a laparoscopic partial left adrenalectomy was performed. Subsequent postoperative pathological analysis identified adrenal schwannoma in conjunction with adrenal ganglioneuroma. The patient recovered well and was discharged on postoperative day 4. A routine urology clinic visit was included in his postoperative care plan. During follow-up assessments, CT scans of the left adrenal gland revealed no abnormalities.ConclusionAdrenal schwannoma combined with ganglioneuroma represents an exceptionally rare collision tumor characterized by the absence of typical clinical or imaging features, leading to potential misdiagnosis. Adrenal incidentalomas present as multifaceted conditions, and this case serves to heighten awareness of their intricate nature. Due to the challenges in preoperative differentiation of various adrenal mass types, postoperative pathological analysis is imperative for guiding the subsequent treatment course for the patient.